POLITICAL IMPERIALISM IN THE LANGUAGE OF ROMAN LAW - Vujović, Ognjen (Political Review, 2023)
The paper represents the continuation of the research that the author had begun earlier on this topic. The subject of research is the terminology of Roman law which served as an excuse for Roman imperial ambitions and goals. The terminology that the Romans used has been found in laws and documents. They were in the service of imperial political manipulation in the frame of the Roman imperial understanding of freedom. Friendship (familiaritas), fairness (iustitia),and the wealth of the province (utilitas provinciae). These terms help eliminate the ideas of nationalities of the conquered people. It can be noted that in none of these examples, the interest of Rome has been stated. We can assume that it was in priority. After all, all roads lead to Rome. These notions allowthe creation of one unique identity, the identity of the Roman Commonwealth. Parallel to the research of these terminologies there will be a comparison to modern-day terminology in the use of Great Powers. Besides these there will also be used historical method, dogmatic method, and political method.